Tick-borne Disease Risk and Recreational Choice – Choice Experiment Data - Slunge, Daniel (University of Gothenburg, 2019)
This dataset is based on a choice experiment on tick-borne disease risk and recreational choice. It contains the variables used in the study “Valuation When Baselines Are Changing: Tick-borne Disease Risk and Recreational Choice” as well as data on additional variables collection in a survey with 1579 respondents in Sweden in 2013.

Understanding how changes in baseline risk influence preferences for risk reduction is important when valuing the welfare effects of environmental change, including the spread of disease. We conduct a survey-based choice experiment among respondents residing in areas with different prevalence of ticks and incidence of Lyme borreliosis (LB) and tick-borne encephalitis (TBE) in Sweden. Respondents face a trade-off between risk and travel cost when choosing between visiting recreational areas differing in prevalence of ticks and disease incidence. Our study indicates that ticks and the risk of tick-borne diseases significantly influence the choice of recreational area and have non-trivial welfare effects. The mean willingness to pay (WTP) per trip to avoid areas with ticks and an incidence of LB of 500 yearly cases per 100 000 inhabitants is estimated at 24 EUR. When there is also a high incidence of TBE the WTP rises to 78 EUR. The WTP for risk reduction is significantly lower among respondents residing in risk areas compared to respondents in emerging risk areas. Explanations for these differences in WTP for risk reduction between groups with different baseline risks include differences in reference point utility, knowledge and learning, leading to adaptation of behaviour and preferences.

Purpose:

The purpose of this paper is to estimate Willingness to Pay (WTP) to reduce the risk of getting tick bites or contracting TBE and LB in connection with visits to recreational areas in Sweden, and to analyze the role of baseline risk and adaptive behaviour for these estimates. We conduct a survey-based choice experiment on recreational choices to derive the WTP for reducing said risks.

This data is based on a survey based choice experiment on tick-borne disease risk and recreational choice. The dataset contains responses from 1579 people in Sweden to an online survey in October 2013. The dataset contains 33159 observations as all respondents answered seven choice sets with three alternatives. The dataset contains 168 variables.

Vi analyserar betalningsviljan för att undvika områden med fästingar samt borrelia- och TBE-risk. I Norrlandslänen där förekomsten av fästingar är relativt ny är betalningsviljan för att undvika risk väsentligt högre än i andra län. Vi finner även att TBE vaccinerade respondenter har en lägre betalningsvilja. Dessa skillnader i betalningsvilja för riskreducering bör beaktas vid ekonomisk värdering av nya risker orsakade av miljö- och klimatförändringar.

Syfte:

Att analysera betalningsviljan för att minska risken för fästingbett, fästingburen encefalit (TBE) och borrelios i samband med friluftsaktiviteter i Sverige.
Fästingburna sjukdomar och friluftsbeteende - survey data från ett valexperiment
Keywords: risk; risk; Ticks; Fästingar; Tick-Borne Diseases; Fästingburna sjukdomar; Choice Behavior; Valbeteende; RECREATIONAL ACTIVITIES/AREAS; stated preference; angiven preferens; Medical and Health Sciences; Medicin och hälsovetenskap; Social Sciences; Samhällsvetenskap